The infinite variety - Attenborough, Richard, 1926-; British Broadcasting Corporation (Wilmette : Films Inc., 1981)
Attenborough attemps to explain where, when, and in what order the earth's more than four million species evolved. Includes a trip to Galapagos Islands and a visual reconstruction of the path of evolution from the first living molecule
Keywords: Evolution; Life -- Origin